PENGARUH INFUSA REBUSAN DAUN KELOR (Moringa oleifera) TERHADAP PENURUNAN KADAR ASAM URAT DALAM DARAH PADA HEWAN COBA MENCIT JANTAN (Mus musculus) - Izal Zahran; Ayyub Harly Nurung; Abd Razak; Rusli Rusli (Fakultas Farmasi UMI, 2022)
Gout is the result of metabolism in the body whose levels should not be excessive, everyone has uric acid in their body, because every normal metabolism will produce uric acid while the trigger is food factors and other compounds that contain lots of purines. The purpose of this study was to determine the effect of giving Moringa oleifera leaf infusion on blood uric acid levels in mice using 25 mice which were divided into 5 groups, namely the positive control group, the infusion 20%, and the infusion 40%, infusion 60% and negative control with treatment for 3 weeks. Measurement of uric acid levels using an autocheck tool. The results of the measurement of uric acid levels in the infusion group 20% showed an average decrease of 0.16 mg/dl, in the 40% group the infusion showed an average value of 0.62 mg/dl and in the infusion group 60% showed an average value of 0.92 mg/dl. The higher the concentration of Moringa oleifera infusion, the lower the uric acid level